2016
DOI: 10.4314/tjpr.v15i7.6
|View full text |Cite
|
Sign up to set email alerts
|

Expressions and clinic significance of miRNA-143, miRNA- 34A, miRNA-944, miRNA-101 and miRNA-218 in cervical cancer tissues

Abstract: 75 and 0.73 (n = 10), 382 and 2.72 (n = 25), 912.9 and 3.93 (n = 21), 1675 and 5.87 (n = 29), and 2120 and 6.66 (n = 11), respectively. Furthermore, qRT-PCR results showed that the expressions of miRNA-944 and miRNA-218 in cervical cancer tissues were markedly up-regulated compared to normal control tissues (p < 0.01). In contrast, the expression level of . Conclusion: The biomarkers, can be considered novel for early diagnosis of cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…miRNAs are a class of small endogenous non-coding single-stranded RNA molecule that widely exist in organisms, with a length of about 19-25 nucleotides [10] . It mainly combines with the 3 'untranslated region (3' UTR) speci city of target gene mRNA in the complete or incomplete pairing manner, leading to direct degradation of target gene mRNA or inhibition of translation of target protein, so as to promote or inhibit gene expression at the post transcriptional level [11][12][13][14] . Many studies have shown the abnormal expression of miRNA in prostate cancer, gastric cancer, non-small cell lung cancer, breast cancer, pancreatic cancer and other tumors [14][15][16] .This abnormal expression affects tumor cell proliferation, apoptosis, migration and invasion, and is closely related to the clinical staging and prognosis of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are a class of small endogenous non-coding single-stranded RNA molecule that widely exist in organisms, with a length of about 19-25 nucleotides [10] . It mainly combines with the 3 'untranslated region (3' UTR) speci city of target gene mRNA in the complete or incomplete pairing manner, leading to direct degradation of target gene mRNA or inhibition of translation of target protein, so as to promote or inhibit gene expression at the post transcriptional level [11][12][13][14] . Many studies have shown the abnormal expression of miRNA in prostate cancer, gastric cancer, non-small cell lung cancer, breast cancer, pancreatic cancer and other tumors [14][15][16] .This abnormal expression affects tumor cell proliferation, apoptosis, migration and invasion, and is closely related to the clinical staging and prognosis of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Human periodontal ligament stem cells (hPDLSCs) from periodontal ligament tissue can form new periodontal supporting tissues and exert effects on the functional regeneration and biological repair of periodontal tissue [2]. MiRNAs are classified of short noncoding RNAs (18-25 nucleotides), which function as gene suppressors to downregulate the stability or translational efficiency of target genes by the 3'-untranslated region (3'-UTR), and can regulate cell proliferation, migration, and differentiation [3,4].…”
Section: Introductionmentioning
confidence: 99%